Writers and rebels the literature of insurgency in the Caucasus - Gould, Rebecca Ruth (New Haven London Yale University Press, 2016)
The Caucasus as region, literature as method -- The Abrek in Soviet Chechen literature -- Regulating rebellion : miracles, insurgency, and Daghestani modernity -- The Georgian poetics of insurgency : redeeming treachery -- Violence as recognition, recognition as violence -- Transgression as sanctity?
Keywords: Caucasian literature -- 20th century -- History and criticism; Insurgency in literature; Violence in literature; Caucasian literature -- 19th century -- History and criticism; Aufstand <Motiv>; Kaukasus